EFFECTIVENESS OF CHROMATOGRAPHY EXTRACT MOMORDICA CHARANTIA ON GREATER WEIGHT RAT CONDITION OF DIABETES MELLITUS - Bour, Cyrilus Jefferson; Sudimartini, Luh Made; Suartha, I Nyoman (Buletin Veteriner Udayana, 2019)
The purpose of this research is to identify the effects the provision of faction chromatography extract of Momordica charantia on the increase in body weight white male diabetes mellitus rats. Momordica charantia extracted using ethanol 70%, then partitioned with n-hexane, and continued with thin layer chromatography, to achieve five factions. 40 white male rats ( Rattus novergicus ) of 3-4-month-old with 150-200 g of body weight were adapted for two weeks, arranged to eight the treatment groups which each group consists of 5 rats. Every treatment was checked blood glucose levels and the average of body weight on the day -1, 0 (hiperglikemia rats), 4, 11, 18. The condition of diabetes mellitus in every group except the negative control that was made by injecting streptozotocin (STZ) on day 0 at a dose of 45 mg/kg. The results of the study showed that the faction 1 and 5 pare fruit doses 50 mg/kg bb able to increased high significantly weight mice on the day 4 th .. equal such as extract ethanol of pare fruit. Faction 2, 3 and 4 pieces pare with the same dosage are able to increase high significantly weight on the day 11 th century. In conclusion, the results showed faction treatment 1 and 5 were faster respond of increasing weight compared with other fractions.